The recontextualising of pedagogic discourse: a case study drawn from an inservice mathematics education project - Davis, Zain (School of Education, 2016)
The dissertation is concerned with the production of a systematic account of the recontextualising of pedagogic discourse across two contexts: mathematics INSET provision and school mathematics teaching. Drawing on the work of sociologists Basil Bernstein and Paul Dowling, an attempt is made to construct a theoretical model which is applied to produce a reading of the interactions between an INSET provider and a teacher, and the teacher and school students. The dissertation opens with a description and discussion of the conceptualising of the research project, the production of data, and the use of the literature survey and theoretical resources in the production of a methodology. The second chapter presents a review of the literature on INSET in which three chief components of conceptions of good INSET practice are highlighted: teachers should define their own needs; INSET should be concerned with the professional development of teachers, where professionalism implies an exclusion or marginalising of academic concerns; and INSET should be school-focused. The chapter moves on to consider NGO-provided INSET and concludes with a discussion of INSET in terms of Bernstein's categories horizontal and vertical discourses. In the third chapter, elements of Bernstein's code theory and Dowling's language of description are appropriated to construct a model which contextualises the study, produces an account of the transmission and acquisition of pedagogic discourse which attends to the interactions between transmitters and acquirers, and generates data for analysis. The chapter concludes with a summary of the model. Chapter 4 is devoted to an analysis of written materials from an INSET course which the teacher attended as well as the interactions between the INSET provider and teacher. An analysis of the use of wall displays and the arrangement of the classroom is produced in chapter 5, followed by an analysis of the interactions between the teacher and students. The analysis focuses on the way in which the utterances of the transmitter and acquirer are redescribed to produce pedagogic texts. The dissertation is concluded in chapter 6 which opens with a discussion of the resources and strategies implicated in the recontextualising of pedagogic discourse after which a summary of the analysis is produced. The last section of the chapter discusses the limitations of the research and the model.